Analisis Pengaruh ROE, NPL, Kebijakan Suku Bunga Terhadap Fluktuasi Harga Saham Perbankan BUMN - Tiara Yuliana Bakris; Riyandi Nur Sumawidjaja (TIN: Terapan Informatika Nusantara, 2026)
Fluctuations in BUMN banking stock prices, driven by internal performance and macroeconomics, create uncertainty for market participants, necessitating further analysis of the influencing factors. This analysis examines the impact of Return on Equity (ROE), Non-Performing Loans (NPL), & Interest Rate Policy on the stock price in BUMN banking in the Indonesia Stock Exchange (IDX) from 2017-2024. The method applied is quantitative using an associative approach. The research utilized secondary data collected from annual reports, the website of Bank Indonesia, and the IDX as sources of information for the analysis data. Analysis stages included descriptive statistical tests, classical assumption tests, multiple linear regression analysis, the coefficient of determination R², t-tests, and F-tests using the SPSS 29 data analysis application. Results of the analysis indicate that ROE, NPL, and Interest Rate Policy affect Stock Price simultaneously, through a significance of 0.020 < 0.05. Individually, ROE has no significant impact (Sig. 0.235 > 0.05), NPL has a significant negative impact (Sig. 0.004 < 0.05), and Interest Rate Policy has no significant impact (Sig. 0.182 > 0.05). Adjusted R-Square results indicate that the three-variable regression model from this research contributes 21.6% to Stock Price, while another 78.4% are influenced by factors outside the scope of the research regression model. These outcomes are expected to develop financial literature on capital markets and guide BUMN banking in mitigating credit risk to maintain stock price stability.